Early-Holocene Episodic Sedimentary Process on the East Hainan Coast: High-Resolution Chronological Refinement, Titanium Intensity and Flux Implications - Mianjin Chen; Xiao Sun; Yang Li; Yulong Xue; Wenzhe Lyu; Xuemu Wang; Yan Li (Journal of Marine Science and Engineering)
Episodic sedimentary processes with significant changes in sedimentation rate have occurred on the East Hainan Coast, the inner shelf of the South China Sea, since the Last Glacial Maximum. In particular, the early-Holocene (~11.5–8.7 ka) rapid sedimentation at a mean rate of ~4.90 m/ka is crucial to understand the processes of terrigenous input to the ocean, carbon cycling and climate control in coastal-neritic sedimentary evolution. However, the chronological framework and the detailed environmental evolution remain uncertain. In this study, core sediments collected from the East Hainan Coast (code: NH01) were used to revisit the characteristics of luminescence signals by comparing the dating results using the blue-light stimulated luminescence (blue-OSL) ages and previously published post-infrared blue-light stimulated luminescence (pIR-blue OSL) ages. The results showed that both the ages agreed with each other for the fine-grained quartz fraction. The refined chronology of the early-Holocene deposits on the East Hainan Coast with higher resolution suggested that the sedimentation rate was ~0.60 m/ka before 10.97 ka, while it increased abruptly to ~5.89 m/ka during the period of 10.97–9.27 ka. According to the refined OSL chronology and the high-resolution (~2.5 cm) titanium intensity using X-ray fluorescence (XRF) scanning, the rapid sedimentation during the early Holocene was likely controlled by increased terrigenous input. The variation in Ti flux reflected the differential response between two meltwater pulse (MWP) events under the combined effects of enhanced early-Holocene monsoons and localized freshwater input. These findings highlight the compound controls of global ice-volume change, monsoon dynamics and coastal geomorphic evolution on sedimentary processes.